"High‐risk" host cell proteins (HCPs): A multi‐company collaborative view. Issue 8 (31st May 2021) - Jones, Marisa; Palackal, Nisha; Wang, Fengqiang; Gaza‐Bulseco, Georgeen; Hurkmans, Karen; Zhao, Yiwei; Chitikila, Carmelata; Clavier, Severine; Liu, Suli; Menesale, Emily; Schonenbach, Nicole S.; Sharma, Satish; et al.
Abstract: Host cell proteins (HCPs) are process‐related impurities that may copurify with biopharmaceutical drug products. Within this class of impurities there are some that are more problematic. These problematic HCPs can be considered high‐risk and can include those that are immunogenic, biologically active, or enzymatically active with the potential to degrade either product molecules or excipients used in formulation. Some have been shown to be difficult to remove by purification. Why should the biopharmaceutical industry worry about these high‐risk HCPs? What approach could be taken to understand the origin of its copurification and address these high‐risk HCPs? To answer these questions, the BioPhorum Development Group HCP Workstream initiated a collaboration among its 26‐company team with the goal of industry alignment around high‐risk HCPs. The information gathered through literature searches, company experiences, and surveys were used to compile a list of frequently seen problematic/high‐risk HCPs. These high‐risk HCPs were further classified based on their potential impact into different risk categories. A step‐by‐step recommendation is provided for establishing a comprehensive control strategy based on risk assessments for monitoring and/or eliminating the known impurity from the process that would be beneficial to the biopharmaceutical industry. Abstract : The authors through a 26‐company collaboration compiled a list of "high‐risk" host cell proteins (HCPs) and classified them based on their potential impact into four different risk categories. A step‐by‐step recommendation was provided for establishing a comprehensive control strategy based on risk assessments for monitoring and/or eliminating the high‐risk HCP from the process. Additionally, this article provides a link to a dynamic web database, which serves as a powerful resource to the biotherapeutic industry in dealing with high‐risk HCPs.